2022
DOI: 10.1002/ange.202203452
|View full text |Cite
|
Sign up to set email alerts
|

Confinement‐Induced Selectivities in Gold(I) Catalysis—The Benefit of Using Bulky Tri‐(ortho‐biaryl)phosphine Ligands

Abstract: The confinement of a catalytic site is an efficient strategy to control a reaction and modulate its selectivity. In the present work, a new class of structurally simple and easily accessible bulky tri-(ortho-biaryl)phosphine ligands were accessed, and their gold(I) complexes synthesized. Their X-ray diffraction analysis and the comparative evaluation of their V Bur % and G steric parameters against a series of gold complexes commonly employed in catalysis demonstrated their confined nature. Despite their notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…In previous studies, we have demonstrated that the cavity-shaped protection enforced by the exceptionally bulky tris-2-(4,4′-di- tert -butylbiphenylyl)phosphine provides a remarkable kinetic stabilization to otherwise unstable compounds, such as the corresponding gold(I)–ethylene and gold(I)-carbonyl complexes of type [(P-ligand)AuL] + (L = C 2 H 4 , CO). 13 On this bases, we now sought to utilize this ligand to access a monomeric Au(I) hydride species, 17 examples of which have been isolated only using strong donor N-heterocyclic carbenes (NHCs) 9a , 18 and NHC-coordinated diphosphene ligands. 19 Gold hydrides have been considered as intermediates in numerous gold-catalyzed organic transformations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, we have demonstrated that the cavity-shaped protection enforced by the exceptionally bulky tris-2-(4,4′-di- tert -butylbiphenylyl)phosphine provides a remarkable kinetic stabilization to otherwise unstable compounds, such as the corresponding gold(I)–ethylene and gold(I)-carbonyl complexes of type [(P-ligand)AuL] + (L = C 2 H 4 , CO). 13 On this bases, we now sought to utilize this ligand to access a monomeric Au(I) hydride species, 17 examples of which have been isolated only using strong donor N-heterocyclic carbenes (NHCs) 9a , 18 and NHC-coordinated diphosphene ligands. 19 Gold hydrides have been considered as intermediates in numerous gold-catalyzed organic transformations.…”
Section: Resultsmentioning
confidence: 99%
“…For elemental analyses, a LECO TruSpec CHN elementary analyzer was utilized. Complex 1 was prepared according to a literature procedure . All other reagents were used as received from commercial suppliers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations